Organoboron Compounds: Effective Antibacterial and Antiparasitic Agents - Paolo Saul Coghi; Yinghuai Zhu; Hongming Xie; Narayan S. Hosmane; Yingjun Zhang (Molecules, 2021)
The unique electron deficiency and coordination property of boron led to a wide range of applications in chemistry, energy research, materials science and the life sciences. The use of boron-containing compounds as pharmaceutical agents has a long history, and recent developments have produced encouraging strides. Boron agents have been used for both radiotherapy and chemotherapy. In radiotherapy, boron neutron capture therapy (BNCT) has been investigated to treat various types of tumors, such as glioblastoma multiforme (GBM) of brain, head and neck tumors, etc. Boron agents playing essential roles in such treatments and other well-established areas have been discussed elsewhere. Organoboron compounds used to treat various diseases besides tumor treatments through BNCT technology have also marked an important milestone. Following the clinical introduction of bortezomib as an anti-cancer agent, benzoxaborole drugs, tavaborole and crisaborole, have been approved for clinical use in the treatments of onychomycosis and atopic dermatitis. Some heterocyclic organoboron compounds represent potentially promising candidates for anti-infective drugs. This review highlights the clinical applications and perspectives of organoboron compounds with the natural boron atoms in disease treatments without neutron irradiation. The main topic focuses on the therapeutic applications of organoboron compounds in the diseases of tuberculosis and antifungal activity, malaria, neglected tropical diseases and cryptosporidiosis and toxoplasmosis.